Sense of coherence (SOC) and social support received by women after mastectomy - Kurowska, Krystyna; Kaczorek, Barbara (Contemporary Oncology/Współczesna Onkologia, 2011)
Background : Breast cancer is not only a medical but also a social problem due to the emotional significance attached to female breasts (attribute of womanhood, symbol of maternity) and the fear of the mutilating procedure of mastectomy. One of the factors that influence one’s ability to cope with the difficult situation resulting from the illness as well as with stress is sense of coherence (SOC). SOC allows one to understand the relationship between the support received by an ill person and their health. A high level of SOC allows patients to see the meaning in life, to believe in life’s order and predictability, which in turn makes them want to be healthy and fully functional. One of the external resources that influence one’s health is social support. The purpose of the study was to assess SOC and the meaning of social support received by women after mastectomy as a determinant of regaining optimum health. Material and methods : The study was conducted at the breast disease ward of the Oncology Centre in Bydgoszcz during which 76 women after mastectomy due to cancer were tested. The SOC level was assessed using Antonovsky’s SOC-29 Questionnaire, whereas the level of social support was measured using the Kmiecik-Baran Scale. Results : The study shows that the level of manageability and meaningfulness varies among women who underwent mastectomy, whereas the level of their comprehensibility and global level of SOC is the same for all the patients. These differences could be observed, however, in relation to the level of social support they received, especially the appraisal and instrumental support. Conclusions : The study will enable better understanding of psychosocial problems of women after mastectomy, whereas recognition of their needs in the scope of support will allow us to compensate for the lack of it and as a result will enable these women to regain optimum health.